ChemInform Abstract: Complementarity of Electronic and Vibrational Circular Dichroism Based on Stereochemical Studies of Vic‐Diols. Issue 18 (April 2016) - Jawiczuk, Magdalena; Gorecki, Marcin; Masnyk, Marek; Frelek, Jadwiga
Abstract: Review: 70 refs.